Die roman maak geskiedenis: Jozef Simons se Eer Vlaanderen vergaat - Morgan, Naòmi (University of the Free State, 2001)
English: Nineteenth-century Romanticism gave birth to both the historical novel and the modern science of history. History and the historical novel continue to be considered incompatible in the most recent articles and theme issues on the subject. From the 1980s onwards, that which characterises the historical novel — recognition for the everyday and the marginal — sparked the interest of historians and historiographers in a history of mentalities and of society, or people’s history. This article focusses on the shared interests of history and the historical novel, using Jozef Simons’s 1927 novel, Eer Vlaanderen vergaat, reprinted in 1999, as its principal textual reference.

Afrikaans: Die negentiende-eeuse Romantiek het geboorte gegee aan sowel die historiese roman as die moderne geskiedeniswetenskap. Geskiedskrywing en historiese romankuns word egter steeds in die mees resente artikels en temanommers as onversoenbaar beskou. Dit wat eie is aan die historiese roman, naamlik erkenning vir dit wat alledaags en marginaal is, het vanaf die 1980s onder historici en historiograwe belangstelling laat ontstaan vir mentaliteits- en maatskappygeskiedenis of “people’s history”. Hierdie artikel fokus op die gedeelde belange van die geskiedskrywing en die historiese romankuns, met as verwysingsteks Jozef Simons se 1927-roman Eer Vlaanderen vergaat, wat in 1999 herdruk is.
Keywords: Historical novel; Simons, Jozef; Eer Vlaanderen vergaat; Modern science of history; Nineteenth-century Romanticism